PENGGUNAAN MODEL PEMBELAJARAN EXAMPLE NON EXAMPLE UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS IV PADA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL DI SD NEGERI 035 SEKELADI KEC. TANAH PUTIH KAB. ROKAN HILIR - Syukri '; Sri Kartikowati; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Abstract: This study is a Class Action Research in Elementary School 035 Sekeladi, the purpose of this study was to determine the implementation of cooperative learning model type Non Example Example in improving students' motivation. Subyek research in fourth grade 035 Sekeladi. From the research, the teacher Increased activity occurs on the implementation of the second cycle, which reached a 87.50% with a category (very good). Aktiviats students also increased, which in the first cycle of student activity only get a 64.81% and increased to 80.86% with both categories (very well). Motivasi also seen increased student learning. This is evident from the percentage of student motivation in the first cycle that only earn a percentage 57.87% in both categories, the increased to 76.39% with the category (very well). Based on the results of the discussion showed that the use of cooperative learning model example of non example is able to increase students' motivation in social studies class IV SD Negeri 035 Sekeladi Tanah Putih Rokan downstream.Keywords: Example non example and Motivation Learning